DEVELOPMENT OF THE INNOVATION POTENTIAL OF THE REGIONAL TOURISM CLUSTER - Tukhtamishov Aziz Kakhramonovich (European Science Publishing, 2024)
The article discusses ways to develop the innovative potential of a regional tourism cluster as one of the key factors in increasing the competitiveness and sustainability of the regional economy. The main attention is paid to the analysis of modern approaches to the formation of an innovative environment, the development of partnerships between cluster members, the introduction of digital technologies and environmentally sustainable practices. Successful examples from the practice of domestic and foreign clusters are considered, as well as recommendations for improving the efficiency of innovation processes are proposed.
Keywords: Innovation potential, regional tourism cluster, tourism development, innovation, digital technologies, sustainable development, partnership, regional economy, tourism industry.